FROM REGIONAL AIRPORT TO INTERNATIONAL FLIGHT DESTINATION: THE CASE OF AALBORG AIRPORT IN NORTHERN DENMARK - Larsen, Gunvor Riber; Lassen, Claus (Journal of Tourism, Sustainability and Well-being, 2017)
This paper explores how Northern Denmark is becoming an international flight destination through the strategic route development in Aalborg Airport and the integrated collaboration with regional tourism actors. Aalborg Airport is primarily a regional airport serving primarily the people living in the northern part of Denmark, but in the past decade the airport has experienced growth in the number of international arrivals. This paper explores who these international travellers are and why they fly to Northern Denmark. Both Aalborg Airport and Northern Denmark in general has an interest in increasing the number of international arrivals, and in the effort to attract more visitors, a better understanding of this group of travellers is necessary. This paper explains that a significant number of the foreign arrivals come to Northern Denmark to visit friends and relatives, and that the geographical reach of the airport is larger than expected. This finding challenges the current approach to regional development associated with the airport and this paper suggests two new focus points for the further strategic route development in Aalborg Airport: awareness of the geographical reach of the airport and incorporation of the knowledge that the international travellers are arriving in order to visit friends and relatives or to do business.